Composition karawitan Bali "Pajegan" | Komposisi Karawitan Bali “Pajegan” - I Nyoman Juniarta; I Nyoman Sudiana; Ni Putu Hartini (GHURNITA: Jurnal Seni Karawitan, 2022)
There are various kinds of things that can make us feel beautiful when we experience them and the various processes that the stylists go through to create pajegan musical works. Pajegan's musical works are inspired by the mapeed tradition in the Kapal Adat Village, the stylists analogize or discuss a form of pajegan into music. Pajegan is a Balinese term which is generally often called Gebogan, which is an offering made to God Almighty or Sang Hyang Widhi Wasa. The process of creating this work is carried out in 3 stages, namely initial stimulation combined with the concept of Alma M. Hawkins in the book consisting of Exploration, Improvisation and Formation. This work is manifested in the form of a pepangulan percussion that remains grounded in the realm of tradition. In this piece of pajegan music using the medium of expressing the Gamelan Gong Kebyar barungan where the number exceeds 30 people, this work is also carried out with an experimental stage process and carries out a systematic development of the motifs of the game.